(untitled) (Cadernos de Sociomuseologia, 2022)
The author presents a reflection on her work experience with Paulo Freire and his team in Cape Verde and Guinea Bissau. Still as an economics student in Lisbon, she remembers her literacy work with the Cape Verdean diaspora. As a member of PAIGC - African Party for the Independence of Guinea and Cape Verde, she would participate in the teams coordinated by Paulo Freire, always bearing in mind the complexity of literacy in these two new countries, which inherited a high level of illiteracy from the colonial period and as this would affect future public policies for Education. Keyword: Literacy; Paulo Freire; Cape Green; Guinea-Bissau, PAIGC;